Perspective: Telehealth – beyond legislation and regulation - Khamis Al-Alawy; Immanuel Azaad Moonesar (SAGE Open Medicine, 2023)
The World Health Organization describes health innovation as developing new or improved systems, policies, products, technologies, services or delivery approaches that improve health and well-being, specifically of vulnerable people. The study’s objectives were to (a) explore the legislative and regulatory journey of telehealth across the Organisation for Economic Co-operation and Development and non-Organisation for Economic Co-operation and Development countries and (b) provide recommendations to strengthen health system performance. We reviewed information sources for Organisation for Economic Co-operation and Development and non-Organisation for Economic Co-operation and Development countries opportunistically, including government and medical board publications, media coverage and peer-reviewed papers, to provide a perspective on the legislative and regulatory telehealth journey. Our review of countries suggests that legislation and regulation remain essential for governance, accountability and assuring that healthcare professionals and technologies are safe and secure. However, there was no uniform approach to telehealth legislation and regulation, and the precautionary approach was observed in some countries. Different strategies appear to have been adopted for telehealth implementation. There is a need to go beyond legislation and regulation to strengthen health system performance and assure the future success of telehealth services. Health system decision makers should work with health system stakeholders to strategise and plan for telehealth services as it will have implications on the future delivery of healthcare services and the health system. Further research is needed to explore how policy frameworks may support innovations in healthcare, such as telehealth.